Hubungan Motivasi Dan Supervisi Terhadap Pencegahan Healthcare Associated Infection (HAIS) Di Masa Pandem (Covid-19) Di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung - Mutia Ade Dea; M. Arifki Zainaro; Dewi Kusumaningsih (Malahayati Nursing Journal, 2022)
ABSTRACT Infections that occur in health facilities or are currently better known as Healthcare-Associated Infections (HAIs) are a serious problem that must be handled. This is due to the large number of infections, which occur after coming to health care facilities. The incidence of HAIs in Lampung Province in 2017 reached 37%, and in 2018 it increased to 42%, RSPBA as one of the private hospitals in Bandar Lampung in 2020 it is known that the incidence of phlebitis reached 0,18, Urinary tract infection (UTI) reached 1.14 and Ventilator-associated pneumonia (VAP) reached 2.18. Internal Medicine Room 3.65% and Surgery Room 5.38%. The purpose of the study was to determine the relationship between motivation and supervision issues in the prevention of Healthcare-Associated Infections (Hais) during the Covid-19 pandemic at Hospital Hospital Pertamina Bintang Amini Kota Bandari Lampung. This type of research is quantitative with a cross-sectional design. The population of this study were all 69 nurses at Pertamina Bintang Amin Hospital, Bandar Lampung City. The sample is 69 respondents. Data collection used in this study was a questionnaire. The statistical test used is the chi-square test with the help of a computer. The frequency distribution of respondents stated that supervision was not good, namely 34 respondents (52.2%), high motivation was as many as 30 respondents (56.5%), the prevention of Healthcare-Associated Infections (HAIS) during the Covid 19 pandemic was good, namely 40 respondents (58.7%), there is an influence of supervision with the prevention efforts of Healthcare-Associated Infections (HAIS) (p-value 0.041. OR 4.3), There is a relationship between motivation and issues of supervision on efforts to Prevent Healthcare-Associated Infections (Hais) during the Covid-19 pandemic Hospitalize Pertamina Bintang Amin Kota Bandar Lampung. Keywords: Motivation, Supervision, Prevention Of Healthcare-Associated Infection (Hais)ABSTRAK Infeksi yang terjadi di fasilitas kesehatan atau yang saat ini lebih dikenal dengan Healthcare Associated Infections (HAIs) adalah masalah serius yang harus ditangani. Hal ini disebabkan karena banyaknya angka kejadian infeksi, yang terjadi setelah datang ke fasilitas layanan.kesehatan. RSPBA sebagai salah satu RS Swasta di Bandar Lampung pada tahun 2020 diketahui angka kejadian Plebitis mencapai 0,18, Infeksi saluran kemih (ISK) mencapai 1,14 dan Ventilator-associated pneumonia (VAP) mencapai 2,18. Ruang Penyakit Dalam 3,65% dan Ruang Bedah 5,38%. Tujuan penelitian adalah untuk mengetahui hubungan motivasi dan supervisi terhadap upaya pencegahan Healthcare Associated Infection (Hais) padai masai pandemii Covidi 19 di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung. Penelitian yang digunakan yaitu kuantitatif sedangkan ini yaitu cross sectional. Populasi di penelitian ini semua perawat di RS Pertamina Bintang Amin Kota Bandar Lampung sebanyak 69 orang.  Pengumpulan data yang digunakan dalam penelitian ini kuesioner. Statistik yang adalah uji chi square dengan bantuan komputer. Distribusi frekuensi responden menyatakan supervisi tidak baik yaitu sebanyak 34 responden (52,2%), motivasi tinggi yaitu sebanyak 30 responden (56,5%), 40 responden (58,7%), Ada pengaruh supervisi dengan upaya pencegahan Healthcare Associated Infections (HAIS), Ada hubungan motivasi dan supervisi terhadap upaya pencegahan Healthcare Associated Infectioni(Hais) pada masa pandemi Covid 19 di Rumah Sakit Pertamina Bintang Amin Kota Bandar Lampung. Kata Kunci: Motivasi, Supervise, Pencegahan Healthcare Associated Infection (HAIs)